Self-Efficacy Tinggi : Bagaimana Kemampuan Komunikasi Matematis Siswa? - Susanti, Dwi; Ervana, Lina; Hermansyah (FKIP Universitas Mataram, 2024)
Mathematical communication skills are important for students to have when solving mathematics problems. Meanwhile, students' mathematical communication skills are related to self-efficacy. Therefore, it was important to carry out an in-depth analysis regarding mathematical communication skills. This research aims to describe students' mathematical communication skills in terms of high self-efficacy. The research method used was qualitative research using a case study approach carried out in class VIII (1) of SMP Negeri 11 Tarakan. Researchers collected data by giving questionnaires, analyzing documents, and conducting interviews. The data analysis technique used is the Miles, Huberman dan Saldana qualitative analysis model. The research results revealed that students' mathematical communication skills included understanding problems, symbolic representation, drawing problem situations, compiling mathematical models, and interpreting problems. The subject understood the problem and found information that was known and asked about it; then the subject could change the information into symbol form and formulate conclusions obtained from solving the problem. The subject determined and explained mathematical concepts and the subject drew or illustrated geometric figures according to the information contained in the question.